Pengaruh Konseling Perawatan Masa Nifas Terhadap Pengetahuan Buku KIA Di Klinik Rosalina Tahun 2025 - Rianita Siagian; Rio Jenita Sipayung; Eka Permatasari Purba; Rizka Sititah Rambe; Hanry Anta Lesmana Meliala (STIKES Columbia Asia Medan, 2025)
Based on the 2017 Indonesian Demographic and Health Survey (SDKI), one of the SDGs targets by 2030 is to reduce the maternal mortality rate to 70 per 100,000 live births. The maternal mortality rate in Indonesia is 305 per 100,000 live births (Ministry of Health, 2017). This community service activity aims to determine the effect of postpartum care counseling on postpartum mothers' knowledge about the use of the KIA handbook. The implementation method involved community outreach and counseling in the target area, with the active participation of community leaders and residents. The results showed that education influenced postpartum mothers' knowledge. Counseling provided to postpartum mothers increased knowledge, leading to changes in knowledge before and after counseling. This activity is expected to be sustainable as a promotive and preventive effort in public health